Regioselective synthesis of 2-(bromomethyl)-5-aryl-thiophene derivatives via palladium (0) catalyzed suzuki cross-coupling reactions: as antithrombotic and haemolytically active molecules - Rizwan, Komal; Zubair, Muhammad; Rasool, Nasir; Ali, Shaukat; Zahoor, Ameer Fawad; Rana, Usman Ali; Shahid, Muhammad; Zia-Ul-Haq, Muhammad; Jaafar, Hawa Z. E. (Chemistry Central, 2014)
BACKGROUND: It is seen that the regioselective functionalizations of halogenated heterocycles play an important role in the synthesis of several types of organic compounds. In this domain, the Suzuki-Miyaura reaction has emerged as a convenient way to build carbon-carbon bonds in synthesizing organic compounds. Some of the most important applications of these reactions can be seen in the synthesis of natural products, and in designing targeted pharmaceutical compounds. Herein, we present the regioselective synthesis of the novel series of 2-(bromomethyl)-5-aryl-thiophenes 3a-i, via Suzuki cross-coupling reactions of various aryl boronic acids with 2-bromo-5-(bromomethyl)thiophene (2). RESULTS: The synthesized compounds were screened for their haemolytic and antithrombolytic activities. The novel compounds 3f, 3i showed highest 69.7, 33.6% haemolysis of blood cells, respectively. The antithrombolytic activity of the compounds was found to be within low to moderate against human blood clot. The compound 3i showed potent clot lysis (31.5%). CONCLUSIONS: Considering these results, it is concluded that the synthesized compounds can be used as a promising source of therapeutic agents.